A strategy for obtaining high electrostrictive properties and its application in barium stannate titanate lead-free ferroelectrics. Issue 17 (1st December 2018) - Jin, Li; Qiao, Jun; Hou, Lei; Tian, Ye; Hu, Qingyuan; Wang, Liang; Lu, Xu; Zhang, Lin; Du, Hongliang; Wei, Xiaoyong; Liu, Gang; Yan, Yan
Abstract: Recently electrostrictive effect in ferroelectrics has attracted much attention, since the electric field-induced strain based on such an effect possesses an ultra-low hysteresis, which is of special interest to both fundamental research and potential application in high-precision actuators. In this paper, we propose a strategy to obtain high electrostrictive properties in ABO3 perovskite structure BaTiO3 (BT)-based ferroelectric ceramics by means of doping. The doping element, amount, valence as well as position are specified according to this strategy. It is suggested that B-site Sn 4+ -doped BT, i.e., Ba(Ti1- x Sn x )O3 (BTS), would possess superior electrostrictive properties. The structural evolution and electrical properties of BTS ferroelectric ceramics were investigated in detail in order to verify this deduction. Besides the ferroelectric-to-relaxor transition with respect to the increase of x from 0.06 to 0.11, expected and high electric field-induced strain (> 0.08% at 40 kV/cm) with a very ultra-low hysteresis (< 8%) is obtained in x  = 0.10–0.11 compositions. High longitudinal electrostrictive coefficient Q 33 ranges from to 0.0398 m 4 /C 2 to 0.0515 m 4 /C 2 accompanying with temperature- and composition-insensitive characteristics. These results not only prove the effectiveness of this strategy, but also pave a way to search for novel kinds of electrostrictive systems in ferroelectrics.